Amine synthesis via transition metal homogeneous catalysed hydrosilylation. Issue 62 (15th June 2016) - Li, Bin; Sortais, Jean-Baptiste; Darcel, Christophe
Abstract : This review summarizes the preparation of amines involving homogeneous transition metal catalysed hydrosilylation including reductions of imines, amides, nitro and nitriles, reductive aminations and N -methylation of amines with CO2 . Abstract : Amines are among the most important compounds due to their wide applications in several areas of importance. Among the numerous synthetic methodologies, this review provides a comprehensive summary of the preparation of amines involving homogeneous transition metal catalysed hydrosilylation methodologies including the reduction of imine, amide, nitro and nitrile derivatives. In addition, challenging tandem reactions such as reductive amination or the use of CO2 as a C1 -building block in N -methylation of amines will also be discussed.